MAGIC and H.E.S.S. detect VHE gamma rays from the blazar OT081 for the first time: a deep multiwavelength study - Manganaro M.; Seglar-Arroyo M.; Becerra González J.; Sanchez D.; Cerruti M.; Tavecchio F.; Fallah-Ramazani V.; Esteban Gutierrez A.; Agudo I.; Ciprini S.; Filippenko A. V.; Hovatta T.; et al. (Italy, 2025)
OT 081 is a luminous blazar well known for its variability in many energy bands. The very-high-energy (VHE; E >100 GeV) gamma-ray emission from the source was discovered by MAGIC and H.E.S.S. during flaring activity in July 2016, after a trigger from the Large Area Telescope (LAT) onboard the Fermi satellite. By analysing the multiwavelength light curves andthe broadband spectral energy distribution (SED), we study the activity of the source and investigate four individual states of activity in the window from MJD 57575 to 57602. The intrinsic gamma-ray spectrum can be described by a power law with spectral indices of 3.27 ± 0.44(MAGIC)and 3.39 ± 0.58(H.E.S.S.) over energy ranges 60–300 GeV and 120–500 GeV, respectively. The combined contemporaneous high-energy (HE;E >100 MeV) through VHE SED shows curvatureand can be described by a log-parabola shape. A simple one-zone synchrotron self-Compton (SSC)model is not sufficient to describe the broadband SED. The presence of broad emission lines in the optical spectrum of the source challenges the categorisation of OT 081 as a BL Lac and, together with the emission scenarios tested, points to the possibility that the source is transitional in nature between a BL Lac and a flat-spectrum radio quasar.
37th International Cosmic Ray Conference (ICRC2021)